A Robust Harmony Search Algorithm Based Markov Model for Node Deployment in Hybrid Wireless Sensor Networks - Mohsen, Abdulqader; Aljoby, Walid; Alenezi, Khaled; Alenezi, Abdulrahman (GEOMATE International Society, 2016)
The performance of the wireless sensor networks, composed of static sensor nodes, is significantly influenced by the random deployment. Often, the sensors are scattered incorrectly and hence positioned inaccurately. A frequent criticism of the random deployment of stationary nodes is that it might cause coverage holes in the field being monitored. In this paper, we propose adding mobile sensor nodes after the initial deployment of the stationary nodes to overcome the coverage holes problem. To achieve optimal coverage, we first described the network dynamics using Markov chain model, and then harmony algorithm is employed to find the optimal solution for the added mobile nodes intended for covering of the holes. The proposed algorithm determines the best locations of the mobile nodes that need to be added after the initial deployment of the stationary nodes. The performance of the proposed algorithm was evaluated using several metrics, and the simulation results demonstrated that, compared to similar state-of-the-art algorithms, the proposed algorithm can optimize the network coverage in terms of the overall coverage ratio, coverage degree and the number of additional mobile nodes.